Implementation Of Character Education In Modern Boarding School Taajussalaam Langkat - Alinafiah, Muhammad; Nurmawati; Sumanti, Solihah Titin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Character education develops the ability to determine good and bad and apply the goodness in life. This study aims to determine the role of Islamic boarding schools in shaping character values in students. This research uses a qualitative method, type of case study single case design. Data collection techniques were carried out by interview, observation and documentation. Data were analyzed using an interactive model consisting of collecting data, reducing data, presenting data, and concluding. Data validity was obtained through the data source triangulation method. The results of this study show that: (1) planning to instill character values according to the foundation of Presidential Regulation No.87 of 2017 with 18 values of character building and national culture (2) implementation by integrating values into the boarding school curriculum is carried out through 3 aspects, namely: through teaching and learning activities, extracurricular activities, and religious activities of santri (2) The implementation of character education in modern Pesantren Taajussalaam these character values include: religious character, discipline, independence, social care, environmental care, tolerance, love of reading, curiosity, communicative / friendly, and responsibility, (3) in the evaluation there are 10 values embedded in the students' personalities (4) the inhibiting factor is the students themselves. The implication of this research is that it has an impact on increasing the personality of students to be better and have Islamic morals, and also on increasing the achievement of students which can be seen from the achievements they achieve.